1997
DOI: 10.1029/97je00518
|View full text |Cite
|
Sign up to set email alerts
|

Applications of spaceborne radar laboratory data to the study of aeolian processes

Abstract: Abstract. Aerodynamic roughness (z0) is an important parameter in studies of sand and dust transport, as well as atmospheric circulation models. Aerodynamic roughness is a function of the size and spacing of surface roughness elements and is typically determined at point locations in the field from wind velocity profiles. Because field measurements require complex logistics, z0 values have been obtained for very few localities. If radar can be used to map z0, estimates can be obtained for large areas. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 30 publications
9
73
0
Order By: Relevance
“…Bold entries are 3-anemometer measurements obtained on the specified date. Literature data are mostly derived from Tables 6 and 7 of Marticorena et al (2006) and Table VIII Greeley et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Bold entries are 3-anemometer measurements obtained on the specified date. Literature data are mostly derived from Tables 6 and 7 of Marticorena et al (2006) and Table VIII Greeley et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Greeley et al [159,160] established relations between z 0 obtained from wind velocity profile data and radar backscatter cross sections. Marticorena et al [161] evaluated the application of a bidirectional reflectance model to estimate roughness properties, while Marticorena et al [162] found a relation between radar backscatter coefficients in the C band and z 0 that suggested potential for remote sensing the roughness length at broad scales.…”
Section: Remote Sensing Approachesmentioning
confidence: 99%
“…Most of the current research on remote sensing-based AR estimations is focused on farmland, forest, and desert regions. Researchers have used the normalized difference vegetation index (NDVI), the airborne Light Detection and Ranging (LIDAR), multi-angle observations, radar backscattering coefficients, and a morphology method to estimate the AR over these land surfaces [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%